2022
DOI: 10.1590/1519-6984.241081
|View full text |Cite
|
Sign up to set email alerts
|

Use of melatonin as an inhibitor of apoptotic process for cryopreservation of zebrafish (Danio rerio) embryos

Abstract: This study investigated the use of melatonin to arrest the effects of apoptosis in vitrified zebrafish (D. rerio) embryos. Dechorionated embryos at 22-24 somite-stage were divided (n = 60/treatment) into a non-vitrified (Control Group, 0 M melatonin) and vitrified treatments with 0 M (T1), 1 µM (T2) and 1 mM of melatonin (T3). For vitrified treatments, a solution methanol/propylene glycol based was used and the embryos stored in -196 °C for a week. After thaw, survival rate, scanning electron microscopy, expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…Moreover, the lethal doses (LD50) at day 3 and day 7 were 32.3 µg/L and 16.4 µg/L, respectively. The control group showed normal development in accordance with Kimmel's description [21]. These results demonstrated that an increase in chromium concentration results in a decrease in zebrafish embryo development.…”
Section: Survival and Hatching Ratesupporting
confidence: 83%
“…Moreover, the lethal doses (LD50) at day 3 and day 7 were 32.3 µg/L and 16.4 µg/L, respectively. The control group showed normal development in accordance with Kimmel's description [21]. These results demonstrated that an increase in chromium concentration results in a decrease in zebrafish embryo development.…”
Section: Survival and Hatching Ratesupporting
confidence: 83%
“…An explanation for the higher success when using an older stage larva, compared with trochophore larva, could be explained by Rusk 42 , who observed minor cell-specific damage and reduced neurogenesis in post-thawed trochophores. Other studies have explained larval mortality after thawing by higher oxidative stress from the production of reactive oxygen species (ROS) during the cryopreservation process 43 45 . Trochophores have higher lipid contents compared with older development stages.…”
Section: Resultsmentioning
confidence: 99%
“…Melatonin (N-acetyl-5-methoxytryptamine) is a hormone secreted from vertebrate pineal gland and regulates homeostasis of reproductive tissues such as ovary and placenta [ 22 ] through receptor-mediated signaling pathways [ 23 ]. Recent studies have reported that melatonin plays a critical role in the cryopreservation of sperm [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], oocytes [ 40 , 41 , 42 , 43 , 44 , 45 , 46 ], and embryos [ 47 , 48 , 49 , 50 , 51 ] in various species. In addition, melatonin is an antioxidant that acts as a free radical scavenger and affects G-protein-coupled receptor-related signaling transduction [ 23 , 52 ].…”
Section: Introductionmentioning
confidence: 99%